Direct and indirect effects of fibroblast growth factor 23 on the heart - Nakano, Toshiaki; Kishimoto, Hiroshi; Tokumoto, Masanori (Frontiers in Endocrinology, 2023)
Fibroblast growth factor (FGF)23 is a bone-derived phosphotropic hormone that regulates phosphate and mineral homeostasis. Recent studies have provided evidence that a high plasma concentration of FGF23 is associated with cardiac disease, including left ventricular hypertrophy (LVH), heart failure, atrial fibrillation, and cardiac death. Experimental studies have shown that FGF23 activates fibroblast growth factor receptor 4 (FGFR4)/phospholipase Cγ/calcineurin/nuclear factor of activated T-cells signaling in cardiomyocytes and induces cardiac hypertrophy in rodents. Activation of FGFR4 by FGF23 normally requires the co-receptor α-klotho, and klotho-independent signaling occurs only under conditions characterized by extremely high FGF23 concentrations. Recent studies have demonstrated that FGF23 activates the renin-angiotensin-aldosterone system (RAAS) and induces LVH, at least in part as a result of lower vitamin D activation. Moreover, crosstalk between FGF23 and RAAS results in the induction of cardiac hypertrophy and fibrosis. In this review, we summarize the results of studies regarding the relationships between FGF23 and cardiac events, and describe the potential direct and indirect mechanisms whereby FGF23 induces LVH.